2012
DOI: 10.3892/or.2012.1746
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HIF-1α in primary gallbladder carcinoma and its relation to vasculogenic mimicry and unfavourable prognosis

Abstract: Abstract.As a novel mode of tumor neovascularization, vasculogenic mimicry (VM) has been reported to increase tumor-related mortality in many different solid tumors. In the present study, two established human gallbladder carcinoma (GBC) cell lines (highly aggressive GBC-SD and poorly aggressive SGC-996) cultured on a three-dimensional matrix were assessed for the ability of VM channel formation under normoxic or hypoxic conditions. In addition, the relationship between HIF-1α gene expression and VM channel fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…VM is a newly-defined tumor microcirculation pattern in some highly aggressive malignant tumors, which differs from endothelium-dependent angiogenesis, and is associated with a poor prognosis for the patients with some aggressive malignancies such as melanoma and gallbladder cancers [11], [14]–[18]. Because VM is an alternative pathway for highly aggressive tumors to guarantee their blood supply, whereas not an angiogenic event arising from pre-existing vessels, it is necessary to find potential therapeutic approaches for targeting VM or in addition to antiangiogenic therapies [23][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…VM is a newly-defined tumor microcirculation pattern in some highly aggressive malignant tumors, which differs from endothelium-dependent angiogenesis, and is associated with a poor prognosis for the patients with some aggressive malignancies such as melanoma and gallbladder cancers [11], [14]–[18]. Because VM is an alternative pathway for highly aggressive tumors to guarantee their blood supply, whereas not an angiogenic event arising from pre-existing vessels, it is necessary to find potential therapeutic approaches for targeting VM or in addition to antiangiogenic therapies [23][25].…”
Section: Discussionmentioning
confidence: 99%
“…Because VM is an alternative pathway for highly aggressive tumors to guarantee their blood supply, whereas not an angiogenic event arising from pre-existing vessels, it is necessary to find potential therapeutic approaches for targeting VM or in addition to antiangiogenic therapies [23][25]. We reported that VM existed in human gallbladder cancers, highly aggressive gallbladder cancer GBC-SD cells and xenografts; whereas poorly aggressive SGC-996 cells did not form the VM networks under the same conditions [13], [17], [18], [42]. In this study, the results showed that NCTD, similar to TIMP-2, inhibited tumor growth and VM formation of GBC-SD xenografts, and prolonged survival time of the xenograft mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VM describes the unique ability of highly aggressive tumor cells, but not poorly aggressive tumor cells, to form matrixrich networks de novo when cultured on a three-dimensional matrix, thus mimicking embryonic vasculogenesis (Maniotis et al 1999). VM, advanced by Maniotis et al (1999), has been described in several other aggressive tumor types, including gallbladder carcinoma (Fan et al 2007), breast cancer (Basu et al 2006), prostate cancer (Sood et al 2001), ovarian carcinoma (Heyman et al 2010), colorectal cancer (Baeten et al 2009), clear cell renal cell carcinoma (Vartanian et al 2009), and acute leukemic bone marrow stromal cells (Mirshahi et al 2009). In recent years, we and others have described the presence of VM in human HCC samples and initiatively investigated its clinical significance (Sun et al 2006;Sun et al 2010;Liu et al 2010).…”
mentioning
confidence: 99%